Amphotericin B-Deoxycholate is as Effective and Safe as the Costly Amphotericin B Colloidal Dispersion in the Treatment of Paediatric Invasive Fungal Infections - Sarinah Tamring; Tey Ie Lane; Hani Syazwani Mohd Shah; Harikrishnan Shanmuganathan; Tzar Mohd Nizam Khaithir; Ahmad Nazrun Shuid; Boekhtiar Borhanuddin; Isa Naina Mohamed (Journal of Pharmacy and Nutrition Sciences, 2014)
Amphotericin B deoxycholate (AmBD) and amphotericin B colloidal dispersion (AmBCD) are the two most commonly used antifungals for invasive fungal infections (IFI) among paediatric patients. The objective of this pilot study was to compare the efficacy, adverse effects and cost-effectiveness between AmBD and AmBCD in the treatment of IFI among paediatric patients admitted at Universiti Kebangsaan Malaysia Medical Centre (UKMMC). Methods: Secondary data analysis of the medical records of all paediatric patients with IFI was obtained and data extraction was performed for patients admitted between July 1, 2006 and June 30, 2011. Efficacy of treatment was determined and reports of adverse effects were noted. Results: Between July 1, 2006 and June 30, 2011, thirty-five patients received AmBD-only treatment and five patients received AmBCD-only treatment. Twenty-four patients were males and the mean age was 7.18 (SD 4.59) years. On average, the AmBCD treatment course was significantly more expensive than AmBD (p<0.01). Patients on AmBD had more adverse effects compared to those on AmBCD. However, there was no significant difference in severe adverse events between these groups. There was no significant difference in efficacy between these groups, in terms of IFI resolution or treatment duration. Conclusion: These findings imply that the use of AmBD instead of AmBCD in IFI treatment among paediatric patients is justified, given its cost-effectiveness, as there was no significant difference in the efficacy or in the incidence of severe adverse effects between these two treatments.